The wild zone : a novel - Fielding, Joy (Atria Books, 2010)
Two brothers -- Will and Jeff -- and their friend Tom are out one night at their favorite South Beach bar, the Wild Zone, and decide to make a bet on who can be the first to seduce a mysterious-looking young woman drinking by herself. Pretty, dark-haired, blue-eyed Suzy has an innocent, almost ordinary girl-next-door way about her. Little do the friends know that their harmless bet is about to take on a life of its own, a life full of deadly consequences for all concerned.